A brine mixing mobile unit in oil and gas industry—An example of a cost-effective, efficient, and environmentally justified technical solution. Issue 23 (1st December 2016) - Perisic, Jasmina; Milovanovic, Marina; Petrovic, Ivana; Radovanovic, Ljiljana; Ristic, Marko; Bugarcic, Marina; Perisic, Velimir
ABSTRACT: The present work shows the technical solution for a mobile unit used for brine mixing in oil and gas industry. Brine is widely used as a fluid when servicing oil and gas wells and pipelines. The use of brine in the process of pipeline overhaul allows safe operation of clogged parts of petroleum wells. In this study, we suggest a technical solution for automated production, storage, and shipping of mentioned brine. The process, methodology, equipment, and implemented "touch panel" application are innovative because they allow cost-effective, efficient, and environmentally safe preparation of brine. The primary goal of the research is to illustrate the use of the mobile unit, as well as innovative importance and usefulness of the process of mixing brine. Furthermore, its aim is to highlight the critical points and possible improvements of described technical solution.